Recent Advances in the Mechanism Research and Clinical Treatment of Anti-Angiogenesis in Biliary Tract Cancer - Wang, Yue; Chen, Tianli; Li, Kangshuai; Mu, Wentao; Liu, Zengli; Shi, Anda; Liu, Jialiang; Zhao, Wei; Lian, Shuo; Huang, Shaohui; Pan, Chang; Zhang, Zongli (Frontiers in Oncology, 2021)
Biliary tract cancers (BTCs), including cholangiocarcinoma (CCA) and gallbladder cancer (GC), are malignancies originating from the biliary tract with poor prognosis. In the early stage of BTCs, surgery is the only choice for cure. Unfortunately, most patients with BTC are diagnosed at an advanced stage and lose the opportunity for surgery. For many advanced solid tumors, antiangiogenic therapy has achieved encouraging results. While most clinical studies on antiangiogenic therapy in advanced BTCs have shown an excellent disease control rate (DCR), the improvement in overall survival (OS) is controversial. Understanding how the relevant signaling molecules influence the angiogenic response and the functional interaction is necessary for the formulation of new treatment regimens and the selection of enrolled patients. In this review, we aim to summarize and discuss the latest advances in antiangeogenesis for BTCs, mainly focusing on the molecular mechanism of angiogenesis in BTCs and the therapeutic effects from clinical trials. Furthermore, the horizon of antiangiogenesis for BTCs is highlighted.